2007
DOI: 10.1002/jmri.20840
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of MR signal and T2* in lung to characterize a tight skin mouse model of emphysema using single‐point imaging

Abstract: Purpose:To evaluate whether MRI signal and T2* measurements of lung tissue acquired at ultrashort detection times (tds) can detect emphysematous changes in lungs. Materials and Methods:MR signal intensity of in vivo mouse lungs was measured at 4.7 T at tds of 0.2 and 0.4 msec using single-point imaging (SPI). T2* was calculated from the measurements obtained at the two tds. Two groups of 8-and 30-week-old Tight Skin (TS) and agedmatched CB57BL/6 mice were examined. The TS mice spontaneously developed emphysema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
60
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 20 publications
11
60
1
Order By: Relevance
“…Indeed, proton MR imaging was successfully applied in experimental animal models of pulmonary emphysema. For example, Olsson et al (11) used single-point imaging to detect structural changes in the lungs using a tight skin experimental model. Similarly, Quintana et al (12) reported decreased MR signal intensities with a gradient-echo sequence in an experimental rat elastase-model of emphysema.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, proton MR imaging was successfully applied in experimental animal models of pulmonary emphysema. For example, Olsson et al (11) used single-point imaging to detect structural changes in the lungs using a tight skin experimental model. Similarly, Quintana et al (12) reported decreased MR signal intensities with a gradient-echo sequence in an experimental rat elastase-model of emphysema.…”
Section: Introductionmentioning
confidence: 99%
“…where SI is measured signal intensity, PD is proton density, and N includes background noise (22). The same fitting analysis performed pixel-wise produced parametric maps of proton density and T2*.…”
Section: Proton Density and T2* With Utementioning
confidence: 99%
“…Since UTE-MRI of the lung was first demonstrated in the early 1990s on a 1.5 T system (28), most of the subsequent studies have been performed on animal MR systems at higher field strengths (14,15,18,22). Only recently, investigators performed UTE-MRI of the lung in animal models using clinical systems at 3.0 T (16,17).…”
Section: Te=01 Ms Te=21 Msmentioning
confidence: 99%
See 2 more Smart Citations